ÁJINIYAZ QOSÍBAY ULÍNÍŃ TÚRKIY XALÍQLAR ÁDEBIYATÍNDA TUTQAN ORNÍ - Kazaxbaev, S. (ILIM hám JÁMIYET, 2025)
The article analyzes the process of studying the work of Ajiniyaz Kosiboy Ogli today on an international scale. Also, some studies about the poet's life and work are discussed in detail.